2021
DOI: 10.26508/lsa.201900332
|View full text |Cite
|
Sign up to set email alerts
|

Kalirin-RAC controls nucleokinetic migration in ADRN-type neuroblastoma

Abstract: The migrational propensity of neuroblastoma is affected by cell identity, but the mechanisms behind the divergence remain unknown. Using RNAi and time-lapse imaging, we show that ADRN-type NB cells exhibit RAC1- and kalirin-dependent nucleokinetic (NUC) migration that relies on several integral components of neuronal migration. Inhibition of NUC migration by RAC1 and kalirin-GEF1 inhibitors occurs without hampering cell proliferation and ADRN identity. Using three clinically relevant expression dichotomies, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 161 publications
(224 reference statements)
0
3
0
Order By: Relevance
“…4c, d, S4e). In line with this, Afanasyeva et al demonstrated decreased migration upon SOX11 knockdown in IMR-32 spheroids, further showing that SOX11 knockdown fosters morphological asymmetric cell divisions and causes reprogramming of nucleokinesis migration in ADRN-type NB cells 19 . To functionally validate the predicted role in control of cytoskeleton and cell migration by our SOX11 overexpression RNA-sequencing data, we performed woundhealing assays confirming that SOX11 overexpression enhances wound healing capacity and migration potential in SH-EP NB cells (Supplementary Fig.…”
Section: The Sox11 Regulated Transcriptome Is Involved In Epigenetic ...mentioning
confidence: 67%
“…4c, d, S4e). In line with this, Afanasyeva et al demonstrated decreased migration upon SOX11 knockdown in IMR-32 spheroids, further showing that SOX11 knockdown fosters morphological asymmetric cell divisions and causes reprogramming of nucleokinesis migration in ADRN-type NB cells 19 . To functionally validate the predicted role in control of cytoskeleton and cell migration by our SOX11 overexpression RNA-sequencing data, we performed woundhealing assays confirming that SOX11 overexpression enhances wound healing capacity and migration potential in SH-EP NB cells (Supplementary Fig.…”
Section: The Sox11 Regulated Transcriptome Is Involved In Epigenetic ...mentioning
confidence: 67%
“…Indeed, SOX11 is regulated by multiple adrenergic specific cis-acting (super-) enhancers, along with adrenergic NBs being strongly dependent on high SOX11 expression levels for growth and proliferation [111]. SOX11 was also shown to be involved in nucleokinesis in adrenergic NB cells [112]. We identified and validated functional SOX11 target genes through genome-wide DNA-binding and transcriptome analysis and identified several genes which are implicated in chromatin remodeling and epigenetic modification.…”
Section: Sox11mentioning
confidence: 94%
“…Re-analysis of NB DNA copy number profiling data revealed the sympatho-adrenal lineage specific SOX11 gene in recurrent chromosome 2p focal gains and amplifications [111]. SOX11 is specifically expressed in adrenergic NBs and absent in mesenchymal NBs [111,112], two distinct superenhancer associated subtypes in NB [135,136]. Indeed, SOX11 is regulated by multiple adrenergic specific cis-acting (super-) enhancers, along with adrenergic NBs being strongly dependent on high SOX11 expression levels for growth and proliferation [111].…”
Section: Sox11mentioning
confidence: 99%